Analisis Perbandingan Kontrol P, PI, dan PID pada Pengaturan Kecepatan Motor DC Berbasis Simulasi MATLAB - Deswen Lumban Gaol; Erianto Rezeki Siregar (CV. KAMPUS AKADEMIK PUBLISING, 2026)
DC motor speed control plays a crucial role in industrial applications requiring fast response, high accuracy, and system stability. This study aims to analyze and compare the performance of P, PI, and PID controllers in a DC motor speed regulation system based on MATLAB/Simulink simulation. The system model was designed in a closed-loop configuration with a 100 rad/s set point, and controller parameters were obtained using the auto-tuning feature to ensure optimal operating conditions. The simulation was carried out for 10 seconds without load by evaluating performance parameters including rise time, overshoot, settling time, steady-state value, and steady-state error. The results indicate that the P controller produces a fast initial response but suffers from high overshoot and low stability. The PI controller demonstrates improved stability with reduced overshoot and shorter settling time, although the steady-state value remains slightly below the set point. The PID controller shows the best overall performance by achieving the fastest rise time, the shortest settling time, and an almost zero steady-state error, making it the most effective in achieving fast, stable, and accurate responses. Therefore, the PID controller is recommended as the most suitable control strategy for DC motor speed regulation under no-load conditions.